The global covariance matrix of tracks fitted with a Kalman filter and an application in detector alignment - Hulsbergen, Wouter (arXiv.org, 2008)
We present an expression for the covariance matrix for the set of state vectors describing a track fitted with a Kalman filter. We demonstrate that this expression facilitates the use of a Kalman filter track model in a minimum \(χ^2\) algorithm for the alignment of tracking detectors. We also show that it allows to incorporate vertex constraints in such a procedure without refitting the tracks.